Integrated Model of Zakat and Waqf for Sustainable Community Development - Lubbi Albar; Yasraf Alam Faidaiyah Faat (Jurnal I-Philanthropy, 2026)
The integration of Zakat and Waqf represents a potent and strategic paradigm shift in Islamic social finance, moving beyond conventional philanthropic models to establish a robust framework for sustainable community development. Zakat, as an obligatory wealth purification and redistribution mechanism, addresses immediate poverty and ensures social justice. Conversely, Waqf, particularly in its productive and cash forms, functions as a perpetual endowment, generating long-term, sustainable assets for public benefit . The synergistic combination of these two instruments Zakat providing working capital and immediate relief, and Waqf supplying the necessary infrastructure and long-term asset base—is crucial for transforming beneficiaries (mustahiq) into self-sufficient economic actors (muzakki). This integrated model is fundamentally aligned with the objectives of Maqasid al-Shariah and the global Sustainable Development Goals (SDGs), particularly in eradicating poverty (SDG 1) and promoting inclusive economic growth (SDG 8). This article proposes a comprehensive integrated model, detailing its conceptual framework, implementation strategies, and the necessary governance structure to optimize its impact on community welfare and economic resilience